Anti-adhesion powder and preparation method thereof

By mixing halogenated polysaccharides with zwitterionic monomers and preparing anti-blocking powders, the problems of fast degradation and poor mechanical properties of existing anti-blocking materials are solved, and better anti-blocking effect and biocompatibility are achieved.

CN119303168APending Publication Date: 2025-01-14SHANDONG UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411318618.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-20
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

Existing anti-adhesion materials such as hyaluronic acid hydrogels and oxidized cellulose membranes have problems such as fast degradation, poor mechanical properties, uneven application and inconvenient adhesion in applications, resulting in limited anti-adhesion effect.

Method used

A mixture of CX-G-ZWY powder and DX-G-ZWY powder was prepared as anti-blocking powder by mixing the halogenated polysaccharide with zwitterionic monomer, catalyzed reaction with CuBr and titrated in methanol. A mixture of CX-G-ZWY powder and DX-G-ZWY powder was prepared as an anti-blocking powder and a curing agent was added to improve the Mechanical strength and degradation cycle to form an anti-adhesion hydrogel.

Benefits of technology

It significantly improves the mechanical strength and degradation cycle of anti-adhesion hydrogel, improves coating uniformity, significantly reduces adhesion scores, and provides better anti-adhesion effect and biocompatibility.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119303168A_ABST
    Figure CN119303168A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of anti-adhesion materials, and discloses anti-adhesion powder and a preparation method thereof, and the preparation method comprises the following steps: mixing halogenated polysaccharide with a zwitterionic monomer, reacting under the catalysis of CuBr, titrating the reaction liquid in methanol after the reaction is completed, and drying the solid obtained by filtration to obtain CX-G-ZWY powder; and the CX-G-ZWY powder and the DX-G-ZWY powder are mixed according to the mass ratio of 1: (0.1-5), and the anti-adhesion powder DX / CX-G-ZWY is obtained. According to the invention, DX-G-ZWY is used as a hydrogel main skeleton, and CX-G-ZWY is added as a curing agent, so that the mechanical strength of the hydrogel is enhanced, and the degradation period of the DX-G-ZWY hydrogel can be effectively prolonged, so that the DX-G-ZWY hydrogel has a good anti-adhesion effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of anti-adhesion materials, and particularly relates to an anti-adhesion powder and a preparation method thereof. Background Art

[0002] The statements herein merely provide background information related to the present invention and do not necessarily constitute prior art.

[0003] Abdominal adhesion is a serious complication after abdominal surgery, which can lead to complex and severe syndromes. Currently, commercial products such as hyaluronic acid (HA) hydrogel and oxidized cellulose membrane (Interceed) are used clinically to improve postoperative adhesion. However, hyaluronidase exists in both the human body and the animal body. This enzyme can easily degrade hyaluronic acid hydrogel, resulting in premature exposure of the damaged area during the wound recovery period, making HA hydrogel unable to completely prevent adhesion and limiting its application range. Oxidized cellulose membrane is inconvenient to use during surgery. For example, it cannot be reused if it sticks to surgical instruments.

[0004] The inventors previously used atom transfer radical polymerization to form a molecular brush structure with zwitterionic monomer polymers and polysaccharide main chains, and used the electrostatic interaction inside the material to form a gel with anti-protein adhesion properties. X -G-ZW Y However, the inventors found that the mechanical properties of this gel are poor, it is easy to degrade, and it is difficult to apply the gel evenly on the wound (the gel with greater mechanical strength is injected from the syringe in a cylindrical shape, has a slow self-healing ability, cannot form a whole, and can only partially cover the wound surface), resulting in poor anti-adhesion effect. In addition, the gel is easy to stick to surgical instruments, which is consumable and labor-intensive, and has the problem of inconvenience in application. Summary of the invention

[0005] In view of the deficiencies in the prior art, the present invention aims to provide an anti-adhesion powder and a preparation method thereof.

[0006] In order to achieve the above object, the present invention is implemented through the following technical solutions:

[0007] In a first aspect, the present invention provides a method for preparing an anti-adhesion powder, comprising the following steps: mixing a halogenated polysaccharide with a zwitterionic monomer, reacting the mixture under the catalysis of CuBr, titrating the reaction solution in methanol after the reaction is completed, and drying the solid obtained by filtration to obtain C X -G-ZW Y powder;

[0008] C X -G-ZW Y Powder and D X -G-ZW YPowder or PSBMA powder is mixed in a mass ratio of 1:0.1-5 to obtain anti-adhesion powder D X / C X -G-ZW Y .

[0009] In some embodiments, D X -G-ZW Y In, D X is a polysaccharide selected from at least one of dextran, starch, heparin, cyclodextrin or hyaluronic acid; ZW Y At least one selected from PSBMA, PCBMA, PCysMA or PTMAO.

[0010] In some embodiments, the D X / C X -G-ZW Y The degree of polymerization is 5-300.

[0011] In some embodiments, C X -G-ZW Y In, C X At least one selected from pentaerythritol, β-cyclodextrin or hydroxypropyl-β-cyclodextrin; ZW Y At least one selected from PSBMA, PCBMA, PCysMA or PTMAO.

[0012] Preferably, C X -G-ZW Y In, C X Pentaerythritol, ZW Y For PSBMA.

[0013] More preferably, C X -G-ZW Y The preparation method is as follows: add 2-bromoisobutyryl bromide to a pentaerythritol solution, react in an ice bath, place the reaction solution in liquid nitrogen, remove oxygen in the reaction solution in vacuo, react at 20-37°C, and purify after the reaction to obtain the initiator Per-Br;

[0014] The Per-Br solution is mixed with the aqueous solution of SBMA, and reacted under the catalysis of CuBr. After the reaction is completed, the reaction solution is titrated in methanol and filtered to obtain Per-g-PSBMA.

[0015] More preferably, the solvent of the pentaerythritol solution is tetrahydrofuran.

[0016] More preferably, the ice bath reaction time is 1.5-3 h, preferably 2 h.

[0017] More preferably, the reaction time at 20-37° C. is 12-48 h, preferably 24 h.

[0018] More preferably, the purification method is: first extract with ether to obtain an extract, then wash the extract with hydrochloric acid solution, saturated sodium carbonate solution and water in sequence, dry the extract, and then rotary evaporate to obtain a crude product, and then recrystallize the crude product with methanol to obtain Per-Br.

[0019] More preferably, the solvent of the Per-Br solution is dimethyl sulfoxide, which forms an interaction force with the ester bond in the structure of the initiator Per-Br.

[0020] More preferably, the molar ratio of Per-Br to SBMA is 1:5-200.

[0021] More preferably, the reaction temperature under CuBr catalysis is 20-37° C., and the reaction time is 12-48 h.

[0022] In a second aspect, the present invention provides an anti-adhesion powder prepared by the preparation method.

[0023] The beneficial effects achieved by one or more embodiments of the present invention are as follows:

[0024] The present invention is based on D X -G-ZW Y As the main skeleton of the hydrogel, C X -G-ZW Y As a curing agent, it can enhance the mechanical strength of the hydrogel and effectively increase D X -G-ZW Y The degradation cycle of the hydrogel gives it a good anti-adhesion effect.

[0025] Specifically, Dex-g-PSBMA is used as the main skeleton of the hydrogel, and pentaerythritol grafted polysulfobetaine polymer (Per-g-PSBMA) is added as a curing agent to enhance the mechanical strength of the hydrogel, and the degradation cycle of the Dex-g-PSBMA hydrogel can be effectively improved, thereby giving it a good anti-adhesion effect.

[0026] PSBMA was used as the main skeleton of the hydrogel, and hydroxypropyl-β-cyclodextrin polysulfobetaine polymer (HP-β-CD-g-PSBMA) was added as a small molecule cross-linker to adjust the mechanical strength of the hydrogel, thereby making it effectively adaptable to postoperative anti-adhesion.

[0027] In the present invention, the anti-adhesion material is prepared into powder (powder has a large and uniform dispersion area, while gel has the disadvantages of uneven distribution and inconvenience in use), which can effectively improve the uniformity of coating and is beneficial to improving its anti-adhesion effect. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.

[0029] Figure 1 This is a photograph of the process of anti-adhesion powder forming glue on the gauze surface in Example 1 of the present invention;

[0030] Figure 2 In Example 1 of the present invention, an anti-intestinal adhesion model is established: a comparison of the abdominal wall and cecum after treatment or without treatment;

[0031] Figure 3 is a flow chart of the gelation of Dex / Per-g-PSBMA powder on the surface of the cecum after the model is established in Example 1 of the present invention;

[0032] Figure 4 is the NMR spectrum of Per and Per-Br in Example 1 of the present invention;

[0033] Figure 5 is the NMR spectrum of Per-g-PSBMA in Example 1 of the present invention;

[0034] Figure 6 These are SEM images of hydrogels with different mass fractions in Example 1 of the present invention, a) Dex0.4 / Per0-g-PSBMA; b) Dex0.4 / Per0.09-g-PSBMA; c) Dex0.4 / Per0.2-g-PSBMA;

[0035] Figure 7 is a comparison chart of the degradation rates of Dex / Per-g-PSBMA hydrogels of different compositions in Example 1 of the present invention;

[0036] Figure 8 is a particle size distribution diagram of the Dex0.4 / Per0.2-g-PSBMA polymer powder in Example 1 of the present invention;

[0037] Fig. 9 is a graph showing the angle of repose of the Dex0.4 / Per0.2-g-PSBMA polymer powder in Example 1 of the present invention;

[0038] Fig.10 is a diagram of a gel powder spraying device in Example 1 of the present invention;

[0039] Fig.11 are photos of the cecum and abdominal wall of each group 7 days after modeling in Example 1 of the present invention;

[0040] Fig.12 1 is a histological examination diagram of the liver, spleen, lung and kidney in Example 1 of the present invention;

[0041] Fig.13 In Example 2 of the present invention, an anti-intestinal adhesion model is established: a comparison of the abdominal wall and cecum after treatment or without treatment;

[0042] Fig.14 is a flow chart of the gelation of PSB / HCD-g-PSBMA powder on the surface of the cecum after the model is established in Example 2 of the present invention;

[0043] Fig.15 is the NMR spectrum of HP-β-CD and HP-β-CD-Br in Example 2 of the present invention;

[0044] Fig.16 is the infrared spectra of HP-β-CD, HP-β-CD-Br, HP-β-CD-g-PSBMA and PSB / HCD-g-PSBMA in Example 2 of the present invention;

[0045] Fig.17 This is a SEM image of the hydrogel for treating intestinal adhesion in Example 2 of the present invention.

[0046] Fig.18 is a graph showing the angle of repose of the PSB / HCD-g-PSBMA polymer powder in Example 2 of the present invention;

[0047] Fig.19 are photos of the cecum and abdominal wall of each group 7 days after modeling in Example 2 of the present invention;

[0048] Fig. 20 These are the H&E staining and Masson staining results of the cecum and abdominal wall tissues of each group 7 days after modeling in Example 2 of the present invention;

[0049] Fig.21 1 is a histological examination diagram of the liver, spleen, lung and kidney in Example 2 of the present invention. DETAILED DESCRIPTION

[0050] It should be noted that the following detailed descriptions are illustrative and intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used in the present invention have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.

[0051] The present invention will be further described below in conjunction with the embodiments.

[0052] Example 1

[0053] Experimental steps:

[0054] (1) Synthesis of high-polymerization degree Dex-g-PSBMA

[0055] The synthesis method is the same as Example 1 of CN202210773927.3, a physical gel based on zwitterion-modified polysaccharides and a preparation method thereof. By changing the feeding amount of SBMA monomer, Dex-g-PSBMA polymers with polymerization degrees of 60, 90, 180 and 240 are finally synthesized.

[0056] (2) Synthesis of initiator Per-Br

[0057] Dissolve 0.5g of pentaerythritol in 30mL of tetrahydrofuran (THF), stir for 60min, add 1.82ml of 2-bromoisobutyryl bromide (BIBB), then put it in an ice bath to react for 2h, put the reaction solution in liquid nitrogen, use a vacuum pump to evacuate the oxygen in the solvent, and then react at room temperature for 24h. After the reaction is completed, add ether to extract, and then wash the mixture with 10% HCl solution, saturated sodium carbonate solution and water respectively. The obtained organic component is dried over anhydrous magnesium sulfate. After rotary evaporation to obtain the crude product, it is recrystallized from methanol to obtain the final product Per-Br as a white solid.

[0058] (3) Synthesis of Per-g-PSBMA

[0059] Weigh 0.05 g Per-Br and dissolve it in 20 mL dimethyl sulfoxide (DMSO). Add 3 mL SBMA / H 2 O mixed solution (sulfobetaine methacrylate (SBMA) concentration is 2.5g SBMA: 3ml H 2 O), add 1.5g CuBr catalyst system, react at room temperature, stir for 24h, titrate in methanol, and filter to obtain the product.

[0060] (4) Preparation of Dex / Per-g-PSBMA

[0061] The synthesized Dex-g-PSBMA and Per-g-PSBMA polymer powders were simply mixed in a certain ratio to obtain a Dex / Per-g-PSBMA powder preparation.

[0062] Physiological saline is added to the Dex / Per-g-PSBMA powder preparation and allowed to stand to obtain a cross-linked and solidified gel.

[0063] (5) The synthesized Per-Br and Per-g-PSBMA polymer powders were dissolved in deuterated DMSO, TMS was used as an internal reference, and 1H-NMR spectroscopy (400 Hz) was used for characterization. Per-Br and Per-g-PSBMA polymer powders were pressed into a potassium bromide pellet using an FT-IR spectrometer at 500-4000 cm -1 characterize within the range.

[0064] (6) SEM observation

[0065] Deionized water was added to the prepared hydrogels with different mass fractions (here, for the characterization of the hydrogel, the powder preparation was first mixed with physiological saline to form a hydrogel, and then the hydrogel was treated, rather than directly characterizing the powder) to allow it to swell to equilibrium. The swollen hydrogel was freeze-dried, quenched with liquid nitrogen and broken into small pieces, and its surface morphology was observed using a scanning electron microscope (SEM) after gold was sprayed on the surface.

[0066] Animal Experiments

[0067] In order to overcome the disadvantages of inconvenient application and uneven smearing of hydrogels, a simpler and more convenient application method was developed for later clinical use. Dex / Per-g-PSBMA powder was applied to the rat abdominal wall-cecum injury model. The in situ gelling properties of Dex / Per-g-PSBMA powder were utilized to apply the powder directly to the injury site to exert anti-adhesion effects, and the first adhesion model was established to explore the anti-adhesion effect of Dex / Per-g-PSBMA powder and study its anti-adhesion mechanism.

[0068] Model establishment: A 5 cm incision was made along the center line of the lower abdominal skin of SD rats, and a 1 cm × 2 cm wound with a depth of about 1 mm was made on the abdominal wall; gauze was used to gently rub the cecum surface corresponding to the abdominal wall wound until the cecum serosa layer was destroyed to the point of obvious punctate bleeding, and the cecum mesentery was sutured and fixed to the upper right corner of the abdominal wall wound with sutures, so that the cecum wound and the abdominal wall wound were aligned to ensure the formation of the adhesion model.

[0069] The hydrogels in each gel group were applied to the injured area with a syringe. The powder group sprinkled the powder on the surface of the cecum with a powder spreading device, and then sprayed additional saline on the surface with a spray bottle (0.5 g of Dex / Per-g-PSBMA powder was evenly sprayed on the surface of the rat cecum, and then 0.5 mL of saline was sprayed). After waiting for about 30 seconds for gelation, the wound was sutured.

[0070] The rats in each group were dissected on the seventh day after surgery to observe the adhesion of the abdominal wall and cecum. Afterwards, the hearts, livers, spleens, lungs and kidneys of the rats were removed and H&E staining of tissue sections was performed to evaluate the biosafety of Dex / Per-g-PSBMA.

[0071] Results section:

[0072] (1) Characterization of polymers and hydrogels

[0073] Per-Br was synthesized by esterification of pentaerythritol with BIBB. 1 H-NMR was used to characterize the structure of the synthesized four-arm initiator, such as Figure 4 As shown, based on the peak area ratio of peak 1 and peak 2, the degree of substitution of Per was determined to be 4.

[0074] Per-g-PSBMA was obtained by grafting the four-arm initiator Per-Br with SBMA monomer via atom transfer radical polymerization (ATRP). 1 H-NMR was used to characterize the structure of Per-g-PSBMA. Its characteristic displacement values ​​are as follows Figure 5 As indicated in the markings.

[0075] Figure 6 In the assay, Dex0.4 / Per0-g-PSBMA is 0.4 g Dex-g-PSBMA mixed with 0.4 ml normal saline to form a gel; Dex0.4 / Per0.09-g-PSBMA is 0.4 g Dex-g-PSBMA + 0.09 g Per-g-PSBMA mixed with 0.6 ml normal saline to form a gel; Dex0.4 / Per0.2-g-PSBMA is 0.4 g Dex-g-PSBMA + 0.2 g Per-g-PSBMA mixed with 0.6 ml normal saline to form a gel.

[0076] Scanning SEM image of freeze-dried gel cross section ( Figure 6 ) showed that gels of different compositions all displayed the unique 3D mesh structure of hydrogels. With the addition of Per-g-PSBMA, the mesh became increasingly dense, shrinking from about 15 μm to about 5 μm, indicating that the addition of Per-g-PSBMA led to an increase in the cross-linking points of the gel network, forming an interpenetrating network of Dex-g-PSBMA and Per-g-PSBMA. Per-g-PSBMA was used as a cross-linker to reinforce the main skeleton of the Dex-g-PSBMA gel.

[0077] like Figure 7 The Dex / Per-g-PSBMA hydrogel was immersed in PBS solution (phosphate buffer solution, pH 7.4). After about 2 days of swelling, the gel degradation accelerated with the infiltration of charges and was completely degraded in about 8 days. After the addition of Per-g-PSBMA crosslinker, the degradation rate of the gel was significantly slower than that of the group without crosslinker. The group without crosslinker was degraded by about 100% on the 8th day, and the degradation rate of the group with crosslinker (Per-g-PSBMA mass percentage was 33%) was about 75% on the 8th day.

[0078] The introduction of cross-linking agents strengthens the gel skeleton and increases the number of cross-linking points. Under the same external ion infiltration, the fewer the original cross-linking points are, the more completely they are destroyed; the more cross-linking points are, the slower the gel skeleton disintegrates.

[0079] Dex0.4 / Per0.2-g-PSBMA powder (0.4 g Dex-g-PSBMA powder and 0.2 g Per-g-PSBMA powder were directly mixed) was ground and sieved, and the average particle size was measured to be about 26.86 μm. Figure 8 As shown; the repose angle of Dex0.4 / Per0.2-g-PSBMA powder is about 55°, as Fig. 9 As shown. Then the powder was placed in the powder spraying device to observe the spraying amount. Among them, the powders that passed the 80-mesh sieve and the 100-mesh sieve could not be sprayed out from the powder spraying device, blocking the nozzle, and because the particles were large, the gelling time was too long. After the powders that passed the 80-mesh sieve and the 100-mesh sieve were sprayed with physiological saline on the surface, the gelling time was about 3 minutes, and the powders that passed the 120-mesh sieve had a gelling time of about 30 seconds. Therefore, it was determined that the powders that passed the 120-mesh sieve were the last ones to pass.

[0080] Initial selection Fig.10 Among the three powder spraying devices, the No. 3 powder spraying device was selected by observing the spraying amount and spraying uniformity. The No. 1 and No. 2 devices sprayed 0.005g of powder each time, and the No. 3 device sprayed about 0.1g of powder each time. Since the amount of Dex0.4 / Per0.2-g-PSBMA powder that needs to be used on the cecum surface each time is 0.5g, considering the frequency of use, the No. 3 device is the better choice. In addition, the powder sprayed by the No. 1 and No. 2 devices is more dispersed, and the powder sprayed by the No. 3 device can be concentrated together (such as Figure 1 ), that is, it can be concentrated on the surface of the cecum, which is convenient for application. Therefore, device No. 3 was selected.

[0081] (2) Evaluation of anti-adhesion effect:

[0082] A standard adhesion scoring system was used: 0 point, no adhesion; 1 point, mild adhesion; 3 points, moderate adhesion; 5 points, severe adhesion.

[0083] Fig.11 In the middle, Model was treated by spraying 1 ml of saline solution after modeling;

[0084] HA hydrogel was applied with 1 ml of HA hydrogel after modeling;

[0085] D / Pg-PSB hydrogel is treated by applying 1 ml of Dex0.4 / Per0.2-g-PSBMA hydrogel after modeling;

[0086] D / Pg-PSB powder was sprayed with 0.5g Dex0.4 / Per0.2-g-PSBMA powder after modeling, and then sprayed with 0.5ml normal saline to make it gel before treatment.

[0087] like Fig.11 As shown in the figure, the saline-treated positive group had severe peritoneal adhesions and obvious ascites. After treatment with commercially available hyaluronic acid hydrogel, the adhesion was reduced compared with the positive control group. This is due to the presence of hyaluronidase, which easily degrades the HA hydrogel, resulting in exposure of the damaged area during the recovery period. Therefore, the anti-adhesion effect is greatly reduced. Only 2 out of 5 animals in the Dex0.4 / Per0.2-g-PSBMA (D / Pg-PSB) hydrogel group had slight adhesions, which was caused by uneven coating during the use of the hydrogel. However, the Dex0.4 / Per0.2-g-PSBMA (D / Pg-PSB) powder group significantly reduced adhesion. On the 7th day after surgery, 4 out of 5 animals had no obvious adhesions, and the adhesion score of animals in the Dex0.4 / Per0.2-g-PSBMA powder group with adhesion was as low as 1 point.

[0088] (3) Biosafety evaluation

[0089] The H&E staining results of the heart, liver, spleen, lungs, and kidneys showed no obvious abnormalities compared with the normal group, such as Fig.12 As shown, it shows that Dex / Per-g-PSBMA (D / Pg-PSB) powder and Dex / Per-g-PSBMA (D / Pg-PSB) hydrogel have good biocompatibility.

[0090] The results showed that Dex / Per-g-PSBMA powders have good anti-intestinal adhesion ability, providing new ideas for clinical application in the prevention of postoperative adhesion.

[0091] Example 2

[0092] Experimental steps:

[0093] (1) Synthesis of initiator HP-β-CD-Br

[0094] Dissolve 1g of hydroxypropyl-β-cyclodextrin in 30mL of tetrahydrofuran (THF), stir for 60min, add 2.28ml of 2-bromoisobutyryl bromide (BIBB), and then place in an ice bath to react for 2h. Place the reaction solution in liquid nitrogen, use a vacuum pump to remove oxygen from the solvent, and then react at room temperature for 24h. After the reaction is completed, dialyze the mixture and freeze-dry to obtain a light yellow powder HP-β-CD-Br.

[0095] (2) Synthesis of HP-β-CD-g-PSBMA

[0096] Weigh 0.1 g HP-β-CD, dissolve it in 20 mL dimethyl sulfoxide (DMSO), add 5 mL SBMA / H 2 O mixed solution (sulfobetaine methacrylate (SBMA) concentration is 3.4g SBMA: 5ml H 2 O), 1.5 g of CuBr catalyst system was added, the reaction was carried out at room temperature, stirred for 24 h, dialyzed for purification, and freeze-dried to obtain HP-β-CD-g-PSBMA polymer powder (HCD-g-PSB).

[0097] (3) Preparation of PSBMA / HP-β-CD-g-PSBMA

[0098] The synthesized 0.3 g PSBMA and 0.2 g HCD-g-PSB polymer powders were simply mixed to obtain a PSBMA 0.3 / HP-β-CD 0.2-g-PSBMA powder formulation (PSB 0.3 / HCD 0.2-g-PSB).

[0099] Physiological saline was added to the PSB 0.3 / HCD 0.2-g-PSB powder preparation and allowed to stand to obtain a cross-linked and solidified gel.

[0100] (4) The synthesized HP-β-CD-Br and HCD-g-PSB polymer powders were pressed into tablets using a potassium bromide pelleting method and spectroscopy was performed using an FT-IR spectrometer at 500-4000 cm -1 characterize within the range.

[0101] (5) SEM observation

[0102] Deionized water was added to the hydrogel powder of the experimental ratio (here, for the characterization of the hydrogel, the powder preparation was first mixed with physiological saline to form a hydrogel, and then the hydrogel was treated, rather than directly characterizing the powder) to allow it to swell to equilibrium. The swollen hydrogel was freeze-dried, quenched with liquid nitrogen and broken into small pieces, and its surface morphology was observed using a scanning electron microscope (SEM) after gold was sprayed on the surface.

[0103] Animal Experiments

[0104] In order to overcome the disadvantages of inconvenient application and uneven smearing of hydrogel, a simpler and more convenient application method was developed for later clinical use. PSB 0.3 / HCD 0.2-g-PSB powder was applied to the rat abdominal wall-cecum injury model. The in situ gelling property of PSB 0.3 / HCD 0.2-g-PSB powder was used directly to the injury site to exert its anti-adhesion effect and establish the first adhesion model to explore the anti-adhesion effect of PSB 0.3 / HCD 0.2-g-PSB powder and study its anti-adhesion mechanism.

[0105] Model establishment: A 5 cm incision was made along the center line of the lower abdominal skin of SD rats, and a 1 cm × 2 cm wound with a depth of about 1 mm was made on the abdominal wall; gauze was used to gently rub the cecum surface corresponding to the abdominal wall wound until the cecum serosa layer was destroyed to the point of obvious punctate bleeding, and the cecum mesentery was sutured and fixed to the upper right corner of the abdominal wall wound with sutures, so that the cecum wound and the abdominal wall wound were aligned to ensure the formation of the adhesion model.

[0106] In each gel group, the hydrogel was applied to the injury site with a syringe. In the powder group, the powder was sprinkled on the surface of the cecum with a powder spreading device, and then additional saline was sprayed on the surface with a spray bottle (0.5 g of PSB 0.3 / HCD0.2-g-PSB powder was evenly sprayed on the surface of the rat cecum, and then 0.5 mL of saline was sprayed). After waiting for about 30 seconds for gelation, the wound was sutured. Fig.14 This is a diagram of the application process of PSB / HCD-g-PSB powder on the cecum surface.

[0107] The rats in each group were dissected on the 7th day after surgery to observe the adhesion of the abdominal wall and cecum. Afterwards, the abdominal wall, cecum, heart, liver, spleen, lung, and kidney were sampled for tissue section H&E staining to further evaluate the adhesion and biocompatibility of PSB / HCD-g-PSB.

[0108] (1) Characterization of polymers and hydrogels

[0109] HP-β-CD-Br was synthesized by esterification of hydroxypropyl-β-cyclodextrin with BIBB. 1 H-NMR was used to characterize the structure of the synthesized macromolecular initiator. Its characteristic shift values ​​are as follows Fig.15 As indicated in the markings.

[0110] HP-β-CD-g-PSBMA was obtained by grafting the macroinitiator HP-β-CD-Br with SBMA monomer via atom transfer radical polymerization (ATRP). The macroinitiator and polymer structure were characterized by FTIR. Fig.16As shown in Figure 2, HP-β-CD-g-PSBMA adds a new 1040 cm -1 The stretching vibration peak belongs to the sulfonic acid group of SBMA.

[0111] Fig.17 The SEM image of the freeze-dried gel cross section showed that the hydrogel prepared by the PSB0.3 / HP-β-CD 0.2-g-PSBMA powder formulation exhibited a 3D mesh structure unique to hydrogels, with uniform and dense meshes of about 5-15 μm.

[0112] After the PSB0.3 / HP-β-CD0.2-g-PSBMA powder is ground, it is passed through the above-mentioned preferred 120 mesh sieve, such as Fig.18 As shown; the angle of repose is approximately 50°.

[0113] (2) Evaluation of anti-adhesion effect:

[0114] A standard adhesion scoring system was used: 0 point, no adhesion; 1 point, mild adhesion; 3 points, moderate adhesion; 5 points, severe adhesion.

[0115] Fig.19 In the middle, Model was treated by spraying 1 ml of saline solution after modeling;

[0116] HA hydrogel was applied with 1 ml of HA hydrogel after modeling;

[0117] PSB / HCD-g-PSB Hydrogel was treated by coating 1 ml of PSB 0.3 / HP-β-CD 0.2-g-PSBMA hydrogel after modeling;

[0118] PSB / HCD-g-PSB Powder was sprayed with 0.5g PSB0.3 / HP-β-CD0.2-g-PSBMA powder after modeling, followed by spraying with 0.5ml normal saline to allow it to gel before treatment.

[0119] The above modeling and treatment results are Fig.13 It is reflected in.

[0120] like Fig.19As shown in the figure, the saline-treated positive group had severe peritoneal adhesions and obvious ascites. After treatment with commercially available hyaluronic acid hydrogel, the adhesion was reduced compared with the positive control group. This is due to the presence of hyaluronidase, which can easily degrade the HA hydrogel, resulting in exposure of the damaged area during the recovery period. Therefore, the anti-adhesion effect is greatly reduced. In the PSBMA0.3 / HP-β-CD 0.2-g-PSBMA (PSB 0.3 / HCD 0.2-g-PSB) hydrogel group, only 2 out of 5 animals had slight adhesions, which was caused by uneven coating during the use of the hydrogel. However, the PSBMA0.3 / HP-β-CD 0.2-g-PSBMA (PSB0.3 / HCD 0.2-g-PSB) powder group significantly reduced adhesion. On the 7th day after surgery, 4 out of 5 animals had no obvious adhesions, and the adhesion score of animals in the PSBMA / HP-β-CD-g-PSBMA powder group with adhesion was as low as 1 point.

[0121] Fig. 20 In the study, H&E staining and Masson staining results showed that compared with the normal group, the saline-treated positive group had severe adhesions between the cecum and abdominal wall, and a large number of inflammatory cells infiltrated around the adhesion tissue; the hyaluronic acid hydrogel-treated group also had similarly tight adhesions between the cecum and abdominal wall, and inflammatory infiltration. The cecum and abdominal wall were completely separated in the PSB0.3 / HCD0.2-g-PSB hydrogel-treated group and the PSB0.3 / HCD0.2-g-PSB powder-treated group. Among them, the epidermis and other tissues in the PSB0.3 / HCD0.2-g-PSB powder-treated group regenerated to form a smoother surface, which was not significantly different from normal tissues.

[0122] (3) Biosafety evaluation

[0123] The H&E staining results of the heart, liver, spleen, lungs, and kidneys showed no obvious abnormalities compared with the normal group, such as Fig.21 As shown, it shows that PSB0.3 / HCD0.2-g-PSB powder and PSB 0.3 / HCD 0.2-g-PSB hydrogel have good biocompatibility.

[0124] The results showed that PSBMA / HP-β-CD-g-PSBMA (PSB / HCD-g-PSB) powder had good anti-intestinal adhesion ability, providing a new idea for its application in clinical prevention of postoperative adhesion.

[0125] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing an anti-adhesion powder, characterized in that: The steps include: The halogenated polysaccharide and the zwitterionic monomer are mixed and reacted under the catalysis of CuBr. After the reaction is completed, the reaction solution is titrated in methanol, and the solid obtained by filtration is dried to obtain C X -G-ZW Y powder; C X -G-ZW Y Powder and D X -G-ZW Y Powder or PSBMA powder is mixed in a mass ratio of 1:0.1-5 to obtain anti-adhesion powder D X / C X -G-ZW Y .

2. The method for preparing the anti-adhesion powder according to claim 1, characterized in that: D X -G-ZW Y In, D X is a polysaccharide selected from at least one of dextran, starch, heparin, cyclodextrin or hyaluronic acid; ZW Y At least one selected from PSBMA, PCBMA, PCysMA or PTMAO; Or, the D X / C X -G-ZW Y The degree of polymerization is 5-300.

3. The method for preparing the anti-adhesion powder according to claim 1, characterized in that: C X -G-ZW Y In, C X At least one selected from pentaerythritol, β-cyclodextrin or hydroxypropyl-β-cyclodextrin; ZW Y At least one selected from PSBMA, PCBMA, PCysMA or PTMAO; Preferably, C X -G-ZW Y In, C X Pentaerythritol, ZW Y for PSBMA; Preferably, C X -G-ZW Y The preparation method is as follows: add 2-bromoisobutyryl bromide to a pentaerythritol solution, react in an ice bath, place the reaction solution in liquid nitrogen, remove oxygen in the reaction solution in vacuo, react at 20-37°C, and purify after the reaction to obtain the initiator Per-Br; The Per-Br solution is mixed with the aqueous solution of SBMA, and reacted under the catalysis of CuBr. After the reaction is completed, the reaction solution is titrated in methanol and filtered to obtain Per-g-PSBMA; The Per-g-PSBMA powder and the Dex-g-PSBMA powder are mixed in a mass ratio of 1:0.1-5 to obtain the anti-adhesion powder Dex / Per-g-PSBMA.

4. The method for preparing the anti-adhesion powder according to claim 3, characterized in that: The solvent of the pentaerythritol solution is tetrahydrofuran.

5. The method for preparing the anti-adhesion powder according to claim 3, characterized in that: The ice bath reaction time is 1.5-3h, preferably 2h; Preferably, the reaction time at 20-37° C. is 12-48 h, preferably 24 h.

6. The method for preparing the anti-adhesion powder according to claim 3, characterized in that: The purification method is: firstly extract with ether to obtain an extract, then wash the extract with hydrochloric acid solution, saturated sodium carbonate solution and water in sequence, dry the extract, and then rotary evaporate to obtain a crude product, and then recrystallize the crude product with methanol to obtain Per-Br.

7. The method for preparing the anti-adhesion powder according to claim 3, characterized in that: The solvent of Per-Br solution is dimethyl sulfoxide.

8. The method for preparing the anti-adhesion powder according to claim 3, characterized in that: The molar ratio of Per-Br to SBMA is 1:5-200.

9. The method for preparing the anti-adhesion powder according to claim 3, characterized in that: The reaction temperature under CuBr catalysis is 20-37°C and the reaction time is 12-48h.

10. An anti-adhesion powder, characterized in that: Prepared by the preparation method described in any one of claims 1 to 9.

Citation Information

Patent Citations

  • Physical gel based on zwitter-ion modified polysaccharide and preparation method thereof

    CN115073770A